2017
DOI: 10.1534/g3.116.035402
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Oxidase Transcription Factors AOD2 and AOD5 ofNeurospora crassaControl the Expression of Genes Involved in Energy Production and Metabolism

Abstract: In Neurospora crassa, blocking the function of the standard mitochondrial electron transport chain results in the induction of an alternative oxidase (AOX). AOX transfers electrons directly from ubiquinol to molecular oxygen. AOX serves as a model of retrograde regulation since it is encoded by a nuclear gene that is regulated in response to signals from mitochondria. The N. crassa transcription factors AOD2 and AOD5 are necessary for the expression of the AOX gene. To gain insight into the mechanism by which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 75 publications
(106 reference statements)
0
11
0
3
Order By: Relevance
“…The production of the AOD1 protein in N. crassa is known to be controlled at the level of transcription of the aod-1 gene [ 19 , 30 , 31 , 33 , 37 ] and at the level of translation of the transcript [ 19 , 37 ]. To distinguish between the two possible mechanisms preventing expression of the protein in Δ yvh1 cells, we analyzed the levels of aod-1 transcript in the deletion mutant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The production of the AOD1 protein in N. crassa is known to be controlled at the level of transcription of the aod-1 gene [ 19 , 30 , 31 , 33 , 37 ] and at the level of translation of the transcript [ 19 , 37 ]. To distinguish between the two possible mechanisms preventing expression of the protein in Δ yvh1 cells, we analyzed the levels of aod-1 transcript in the deletion mutant.…”
Section: Resultsmentioning
confidence: 99%
“…A number of genes that affect aod-1 expression have been identified [ 23 , 28 , 29 ]. Two zinc cluster transcription factors, encoded by the aod-2 and aod-5 genes [ 23 , 30 ], bind constitutively as a heterodimer in the upstream region of the aod-1 gene and are required for the increased transcription of aod-1 that occurs under inducing conditions [ 19 , 30 , 31 , 32 , 33 ]. Similarly, the expression of AOX in Aspergillus nidulans and Podospora anserina requires the orthologues of N. crassa AOD2 and AOD5 [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene rescue experiments, sequencing, and bioinformatics revealed that aod-2 and aod-5 encode zinc cluster transcription factors (Chae et al 2007b). These factors bind constitutively as a heterodimer to an alternative oxidase induction motif (AIM) that exists in the promoter region of the aod-1 gene (Chae et al 2007a; Qi et al 2017). Transcription of aod-1 is induced in response to an unknown signal(s) generated when the standard electron transport chain is disrupted.…”
mentioning
confidence: 99%
“…Transcription of aod-1 is induced in response to an unknown signal(s) generated when the standard electron transport chain is disrupted. In the absence of either aod-2 or aod-5 , the induction of aod-1 is essentially eliminated (Tanton et al 2003; Chae et al 2007a; Chae et al 2007b; Chae and Nargang 2009; Qi et al 2017). Orthologs of the AOD2 and AOD5 proteins exist in other fungi and have been shown to be required for AOX induction in Aspergillus nidulans (Suzuki et al 2012) and Podospora anserina (Bovier et al 2014).…”
mentioning
confidence: 99%